The Roles of Entrepreneurial Competencies and organizational Life Cycle Stages in Malaysian Tourism and Hospitality SMEs: A Proposed Framework - Victoria, Jonathan; Hahn, Huh-Jung; Ardichvili, Alexandre (2016)
Small and medium enterprises (SMEs) in the tourism and hospitality industry are important contributors to the development of the Malaysian economy. Despite considerable support and incentives provided by the government, many SMEs still fail at different stages of their ventures. Since successful SMEs have a huge impact on a nation’s growth and economic well being, it is therefore critical to understand predictors of SME success. Some scholars attribute SME success to the competencies of the entrepreneurs themselves. This working paper proposes a conceptual framework for further empirical investigation. The framework integrates existing gaps in entrepreneurial SMEs by examining competencies required at different stages of SME growth, taking into consideration the uniqueness of the industry and the Malaysian context. The proposed framework is also anticipated for use by entrepreneurs, educators and trainers to develop the required competencies to facilitate SME growth and success. Keywords: SME; entrepreneurial competencies; Malaysia; tourism and hospitality industry